Iran Millennium Development Goal's in a Glance - GhR Heidari; RN Heidari (Tehran University of Medical Sciences, 2009)
"nThe Millennium Development Goal's (MDG's) represent a global partnership that has grown from the comments and targets established at the world summits of the 1990's. Responding to the world's main development challenges and to the calls of civil society, the MDG's promote poverty reduction, education, maternal health, gender equality , and aims  at combating child mortality, AIDs and other diseases, environmental sustainability and global partnership. Set for the year 2015, the MDG's are an agreed set of goals that can be achieved if all actors work together and do their part. Poor countries have pledged to govern better, and to invest in their people through health care and education. Rich countries have pledged to support poor countries through aid, debt relief and fairer trade. MDG's at the Ministry of Health and Medical Education in Iran aims to, reduce the under- five mortality rate to two thirds between 1990 and 2015,  improve maternal health by reducing to three quarters the mortality ratio and  achieve universal access to reproductive health, to combat  HIV/AIDS, Malaria, and TB, and  to have them halted by 2015, to reverse the spread of HIV/AIDS and to achieve by 2010 a universal access to treatment to all those who need it and  by 2015 begin to reverse the incidence of malaria and TB.